Intracontinental Orogeny Enhanced by Far‐Field Extension and Local Weak Crust. Issue 12 (5th December 2018) - Silva, David; Piazolo, Sandra; Daczko, Nathan R.; Houseman, Gregory; Raimondo, Tom; Evans, Lynn
Abstract: The accommodation of intraplate stresses in preexisting weak regions of plate interiors is here investigated using thin viscous sheet numerical models. The intraplate stresses are governed by multicomponent and multidirectional stresses originating at plate boundaries. The modeled scenarios mimic plate boundary conditions during the intraplate Alice Springs Orogeny (ASO), central Australia, and include (1) a northwest‐southeast zone of weak lithosphere within strong continental blocks to the north and southand (2) a principal south directed stress condition at the northern boundary that causes minor clockwise rotation of the northern block. Alternative tectonic environments are investigated in additional models that include (1) secondary compressional or extensional stresses acting at the eastern boundary, representing the temporally variable stress conditions during the Tasmanides Orogeny, and (2) an eastern wedge‐shaped zone of rheologically weak lithosphere, mirroring rift fill of the Irindina subbasin. Our results highlight that a low angle between major crustal features (e.g., orogenic elongation and preexisting regional structures) and the principal transmitted stresses is highly relevant in the concentration of elevated levels of differential stress and subsequent localization of deformation in plate interiors. Secondary stresses orthogonal to the principal acting stresses may introduce effects that explain the episodic orogenic activity in the case of the ASO. The combination of secondary extensional stresses at the eastern boundary of Australia and weak lithosphere of the preexisting Irindina subbasin strongly influences the observed spatial strain intensity, localization, and kinematics of deformation during the ASO. Key Points: We investigated the intracontinental orogeny enabled by preexisting intraplate crustal zones of weakness at low angle to subsequent principal stresses Secondary stresses, orthogonal to the principal stress, are important in the episodic development and evolution of intracontinental orogeny Extensional secondary stresses enhance the lateral extrusion of lower crustal material from weak areas